Pengaruh Tingkat Pelayanan, Solidaritas, dan Kemampuan Bersaing Koperasi terhadap Partisipasi Anggota pada Koperasi Pegawai Republik Indonesia - Muhammad Rizki E; Yulhendri Yulhendri (Jurnal Ecogen, 2020)
This study was conducted to determine the effect of the level of service, solidarity, and the competitive ability of cooperatives to the participation of members of the KPRI Disdik West Sumatra. This research is a type descriptive and associative. The population in this study were members of the Cooperative Employees of the Republic of Indonesia (KPRI) Departement of Education in the Province of West Sumatera with a total population of 1.142 cooperative member and a sample of 92 cooperative members. Test the validity of using SPSS version 25, shown in column corrected item-total correlation and reliability testing are shown in column Cronbach alpha. The data analysis technique used is multiple linear regression. To test the hypothesis used T test using SPSS version 25. The results showed that (1) Level of Services significantly influence the Members Participation KPRI Disdik Sumatra Barat. (2) solidarity has a significant influence on the participation of member of the KPRI Disdik Sumatera Barat. (3) the ability to compete cooperatives has a significant influence on the participation of members KPRI Disdik Sumatera Barat.Keywords : sevice level, solidarity, cooperative competitiveness, member partcipation